Proteomic Insights on the Metabolism of Penicillium janczewskii during the Biotransformation of the Plant Terpenoid Labdanolic Acid - Martins, Isabel; Varela, Adélia; Frija, Luís M. T.; Estevão, Mónica A. S.; Planchon, Sébastien; Renaut, Jenny; Afonso, Carlos A. M.; Silva Pereira, Cristina (Frontiers in Bioengineering and Biotechnology, 2017)
Plant terpenoids compose a natural source of chemodiversity of exceptional value. Many of these compounds own biological/pharmacological activity, others are regarded as unique chemical skeletons for the synthesis of derivatives with improved properties. Functional chemical modification of terpenoids through biotransformation frequently relies on the use of Ascomycota strains but information on major cellular responses is still largely lacking. Penicillium janczewskii mediates a stereo-selective hydroxylation of labdanolic acid - terpenoid found abundantly in Cistus ladanifer - producing 3β hydroxy-labdanolic acid with yields >90%. Herein, combined analyses of mycelial and extracellular differential proteomes demonstrated that the plant terpenoid increased stress-responses, especially against oxidative stress (e.g. accumulation of superoxide dismutase) and apparently altered mitochondria functioning. One putative cytochrome P450 monooxygenase differentially accumulated in the secretome and the terpenoid bioconversion was inhibited in vivo in the presence of a P450 inhibitor. The stereo-selective hydroxylation of the plant terpenoid is likely mediated by P450 enzymes, yet its unequivocal identity remains unclear. To the best of our knowledge this is the first time that proteomics was used to investigate how a plant terpenoid impacts the metabolism of a filamentous fungus during its efficiently biotransformation. Our findings may encourage development of new strategies for the valorisation of plant natural resources through biotechnology.